Comparison of Analgesic Efficacy Between Transversus Abdominis Plane Block and Epidural Following Abdominal Surgery - Tariq, Haroon; Muhammad Rashid Iqbal; Khan, Rao Ali Shan; Muhammad Saeed; Ameer Yasser Zaid; Mehmood, Tariq (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare post-operative analgesic efficacy of ultrasound guided transversus abdominis plane (TAP) block versus intra-thoracic epidural catheter in patients undergoing abdominal laparotomy. Study Design: Quasi experimental study. Place and Duration of Study: Department of Anesthesia, Combined Military Hospital (CMH), Rawalpindi, Pakistan, from Apr to Sep 2023. Methodology: An 18 Gauge (G) Smith epidural catheter Touhy needle was inserted pre-operatively in the epidural (T6 thoracic) space by a consultant anesthetist, under aseptic measures, with patient in the sitting position, and catheter secured after correct placement. Bilateral TAP block was performed in all patients who underwent abdominal surgery and 15 ml of 1% lignocaine with adrenaline was injected on each side of the block. Primary variable was mean time to first rescue analgesia and measurement of patient satisfaction in both groups. Results: Mean time to first post-operative rescue analgesia requirement by patients showed a mean time of 558.38±14.53 minutes in the TAP block group versus 345.85±19.77 minutes in the epidural group (p<0.00). Mean time of stay in the High Dependency Unit (HDU) showed a mean stay of 27.80±2.35 hours in the TAP group versus 43.97±5.21 hours in the epidural group (p<0.00). Conclusion: TAP block provided effective analgesia with better HDU stay and superior patient satisfaction when compared with epidural analgesia.